Rancang Ulang Saluran Drainase Kampung Lalang dengan Metode Drainase Biopori Resapan - Fikri Auza’I Ikhwan; Rizky Franchitika (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2021)
Drainage is one of the infrastructure facilities for people’s lives in urban areas, but unfortunately there are many drainages that do not function properly so that drainage seems useless. One of the functions of drainage is as a building to prevent flooding and control water in an area, but in fact floods still occur, one of which is in the Kampung Lalang area, where one of the causes is the mismatch between the flood discharge and the size of the channel dimensions. Biopore infiltration drainage is one solution to overcome this problem where some of the overflow water will be returned to groundwater.